NARRATIVES OF GROWTH MINDSET AMONG HIGH SCHOOL STUDENTS WITH HIGH MATHEMATICS ANXIETY - Usman, Muhammad Rizal; Satriani, Sri; Sukmawati, Sukmawati; Kristiawati, Kristiawati (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
Mathematics anxiety is one of the major barriers to students’ achievement and positive attitudes toward learning mathematics. Conversely, a growth mindset is considered a protective factor that fosters learning resilience. This study aims to explore the narratives of students with high levels of mathematics anxiety in relation to their growth mindset. A qualitative narrative approach was employed with three 11th-grade high school students in Malang Regency, Indonesia, selected purposively based on their scores on the Math Anxiety Questionnaire (MAQ). Data were collected through semi-structured interviews, written reflections, and field notes, and analyzed using thematic narrative analysis. The findings reveal five major themes: (1) initial negative perceptions of mathematics, (2) emotional responses to failure such as nervousness, frustration, or shame, (3) efforts to recover through diverse coping strategies, (4) social support from teachers, peers, and families that influences resilience, and (5) indications of growth mindset reflected in the belief that effort is more important than innate talent and mistakes are part of the learning process. These results highlight that although high mathematics anxiety poses challenges, a growth mindset can serve as a protective factor in building students’ learning resilience. This study contributes to the literature on the intersection between mathematics anxiety and growth mindset and provides practical implications for teachers to create a classroom climate that fosters positive mindset development.